2013
DOI: 10.1185/03007995.2012.761599
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of different oral iron supplements: a systematic review

Abstract: Extended-release ferrous sulfate with mucoproteose appears to be the best tolerated of the different oral iron supplements evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
188
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(205 citation statements)
references
References 54 publications
3
188
0
14
Order By: Relevance
“…However, placebo controlled studies in pregnant women have shown that ferrous iron doses of 105 mg/day has a side effect profile, which is not significantly different from placebo [47,48]. The slow release iron formulas Ferro Duretter, IberetFolic and ferrous sulphate with mucoproteose (Tardyferon) have fewer gastrointestinal side-effects (nausea, epigastric pain, constipation) than fast release formulas [45,49,50]. Actually, Ferro Duretter has a side effect profile being comparable to placebo tablets [49].…”
Section: Iron Formulas: Fast and Slow Release Formulasmentioning
confidence: 99%
“…However, placebo controlled studies in pregnant women have shown that ferrous iron doses of 105 mg/day has a side effect profile, which is not significantly different from placebo [47,48]. The slow release iron formulas Ferro Duretter, IberetFolic and ferrous sulphate with mucoproteose (Tardyferon) have fewer gastrointestinal side-effects (nausea, epigastric pain, constipation) than fast release formulas [45,49,50]. Actually, Ferro Duretter has a side effect profile being comparable to placebo tablets [49].…”
Section: Iron Formulas: Fast and Slow Release Formulasmentioning
confidence: 99%
“…These preparations have several negative side effects, including gastrointestinal distress (Peña-Rosas et al, 2012;Cancelo-Hidalgo et al, 2013) and changes in the composition of colonic microflora (Zimmermann et al, 2010;Dostal et al, 2012). These methods also result in defects in body structural elements caused by the formation of reactive oxygen species (Kehrer, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…They are likely due to direct toxicity of unabsorbed iron on the intestinal mucosa. Two recent meta-analyses including several thousands of patients receiving ferrous iron salts have reported gastrointestinal AEs in proportion variables from 30 to 70% of cases [56,57]. The ensuing reduction of adherence, in combination with the need of prolonged treatment (see above), results in undertreatment of a significant proportion of IDA patients in daily clinical practice.…”
Section: A Far From Ideal Treatmentmentioning
confidence: 99%